The Role Of Future Anxiety And Self-Efficacy On Final-Year Students' Psychological Well-Being - Umi Laela Mukaromah; Prinska Damara Sastri (Publikasi Indonesia, 2025)
Students are those who attend universities to further their education, and they are responsible for managing and finishing assignments. Students start to assume responsibility for their personal life in addition to their education. That is commonly a cause of excessive stress which in turn leads to anxiety. Future anxiety is the most prevalent type of anxiety that final-year students feel. The motivation of this study was to examine how final-year students' psychological well-being are impacted by their future anxiety and self-efficacy. This study employs quantitative research in the form of a survey. Participants in this research belong to Universitas Indonesia Membangun final-year students. There are 95 participants in all, 15 of whom are males and 80 of whom are women. Data were collected using the future anxiety scale, self-efficacy scale, and psychological well-being scale, all of which were adjusted by the researcher. Statistic Descriptive, Multiple linear regression, and correlation tests were used for analyzing the data. The results of this research shows a correlation between final-year students' psychological well-being, self-efficacy, and future anxiety. When psychological well-being grows, self-efficacy becomes an indicator that can inhibit future anxiety.